2017
DOI: 10.1016/j.cellimm.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

ESC-derived thymic epithelial cells expressing MOG prevents EAE by central and peripheral tolerance mechanisms

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an animal model for multiple sclerosis (MS), and is induced by immunization with disease-causative self-antigens such as myelin oligodendrocyte glycoprotein (MOG). We have previously reported that transplantation of MOG expressing thymic epithelial progenitors (TEPs) derived from 129S6SvEv Tac mouse embryonic stem cells (mESCs) prevented the development of EAE. In this study, we expand our previous studies to show that transplantation of MOG expressing mESC-TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…It is well-known that TECs, especially medullary TECs (mTECs), are involved in the deletion of autoreactive T cells. We have demonstrated that transplantation of ESC-TEPs expressing disease-causative self-antigen results in the deletion of the antigen-specific autoreactive T cells (47,48). Our hypothesis further proposes that transplantation of APP gene-deleted ESC-TEPs would lead to the generation of Aβ-specific autoreactive T cells that could help the production of other Aβ-specific immune cells to clear the Aβ plaques in the CNS.…”
Section: Introductionmentioning
confidence: 69%
“…It is well-known that TECs, especially medullary TECs (mTECs), are involved in the deletion of autoreactive T cells. We have demonstrated that transplantation of ESC-TEPs expressing disease-causative self-antigen results in the deletion of the antigen-specific autoreactive T cells (47,48). Our hypothesis further proposes that transplantation of APP gene-deleted ESC-TEPs would lead to the generation of Aβ-specific autoreactive T cells that could help the production of other Aβ-specific immune cells to clear the Aβ plaques in the CNS.…”
Section: Introductionmentioning
confidence: 69%
“…In the EAE model, it was shown that thymic epithelial expression of proteolipid protein (PLP) contributes to T-cell tolerance to PLP ( 16 ). Furthermore, the intrathymic administration of myelin oligodendrocyte glycoprotein (MOG)-expressing thymic epithelial progenitors induced specific tolerance against this antigen and significantly reduced EAE severity ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this approach can be combined with genetic manipulation of grafted autologous TEPs to ensure that their TEC progeny expresses desired or putative autoantigens and can thus limit thymic escape of potentially pathogenic T cells by fostering their clonal deletion or differentiation into antigen-specific tolerogenic tT reg cells. The potential efficacy of this strategy for CNS autoimmune diseases is supported by a proof-of-concept study in a preclinical model, in which transplantation of embryonic stem cell–derived TEPs engineered to express MOG rendered mice resistant to later EAE induction through deletion of MOG-autoreactive T cells and generation of MOG-specific T reg cells [ 240 ].…”
Section: Therapeutic Implications and Future Directionsmentioning
confidence: 99%